Identifying critical abilities for optimal performance of air traffic controllers: a subject matter expert rating approach. - Jafari Roodbandi, Akram Sadat; Choobineh, Alireza; Nami, Mohammad (International Journal of Occupational Safety & Ergonomics, 2025)
Objectives. Air traffic control (ATC) is a dynamic and cognitively demanding profession involving complex, safety-critical operations that requires managing both expected and unexpected tasks. Beyond cognitive performance, ATC also demands abilities in other domains. This study aimed to identify and rate the abilities essential for optimal ATC performance based on input from subject matter experts (SMEs). Methods. The study utilized the Fleishman job analysis survey (F-JAS), which includes 52 questions on cognitive, sensory-perceptual, psychomotor and physical abilities, and 21 questions on social/interpersonal abilities. Twenty SMEs, with average age 43.5 ± 5.07 years and 20.6 ± 4.3 years of professional experience, rated the required level of each ability in relation to optimum performance in ATC on a 1–7-point scale. Results. Spatial visualization (6.4 ± 0.51) and oral expression (6.22 ± 0.67) in terms of cognitive abilities, reaction time (5.5 ± 0.91) and reaction orientation (5.36 ± 1.06) in terms of psychomotor abilities, and hearing attention (6.27 ± 0.65) and hearing sensitivity (6 ± 0.84) in terms of sensory-perceptual abilities have the highest ability level. Self-control and persistence of effort have the highest rank in social and interpersonal abilities for optimum performance in the ATC job. Conclusions. This study highlights the importance of cognitive, sensory-perceptual and interpersonal skills in ensuring safe and efficient air traffic management.